2013
DOI: 10.5539/jas.v5n4p26
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Water Circulation Period for the Culture of Goldfish with Spinach in Aquaponic System

Abstract: Experiment with varied water circulation periods having 4, 8, 12, and 24 hrs/day as T1, T2, T3 and T4, respectively in aquaponics, evaluated against a control (without aquaponics) revealed higher fish and plant growth in T3 and T4. The mean growth of fish varied significantly among treatments showing higher growth in T4 and control followed by T3, T2 and T1. Survival rate was 100% in all the treatments as well as control. Percentage weight gain, SGR (% day -1 ) also showed the similar trend as that of growth s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
(8 reference statements)
4
7
0
1
Order By: Relevance
“…This finding is in accordance with the result of Shete et al (2013) on culturing goldfish with spinach wherein water circulation can be reduced to 12 hours per day for economically effective aquaponics production and may be considered as optimum water circulation period for goldfish production in the aquaponic system.…”
Section: Methodssupporting
confidence: 88%
“…This finding is in accordance with the result of Shete et al (2013) on culturing goldfish with spinach wherein water circulation can be reduced to 12 hours per day for economically effective aquaponics production and may be considered as optimum water circulation period for goldfish production in the aquaponic system.…”
Section: Methodssupporting
confidence: 88%
“…Considerable growth of Goldfish and Koi carp were observed in this experiment. Growth performance of Goldfish in aquaponics recirculating system was carried out by Shete et al (2013) and observed that weight gain and SGR were comparable with present result. While considering the Koi carp, comparison of growth, survival rate, and number of marketable Koi carp produced under different management regimes were done by Jha, Barat, and Nayak (2006) and comparable results were observed.…”
Section: Discussion Fish Growth Parameterssupporting
confidence: 74%
“…Considering its habitat and the value of nutrient uptake, it can be used efficiently in aquaponic recirculating system. Goldfish and Koi carp have previously been identified as suitable species in monoculture aquaponic recirculating systems (Shete et al, 2013;Shete, Verma, Kohli, Dash, & Tandel, 2014;Hussain et al, 2014Hussain et al, , 2015. There are sufficient evidences in using these species in monoculture aquaponic recycling system; but, there is no published literature available with regard to their polyculture, neither density ratio in aquaponics.…”
Section: Introductionmentioning
confidence: 99%
“…Identical circulating pumps (24 L/min) were used in all six channels and mixed the water in the channels at a rate equal to a hydraulic retention time (HRT) of 8 min. This flow rate maintained good mixing in the channels and roots appeared to be kept under gentle movement, which we did to avoid possible problems of root stress previously mentioned by Shete et al [14]. A crucial part of the hydroponic channels was the nutrient solution reservoir (made with modifications to a cooler chest).…”
Section: The Hydroponic Systemsmentioning
confidence: 99%